2000
DOI: 10.1038/35003595
|View full text |Cite
|
Sign up to set email alerts
|

Delayed activation of the paternal genome during seed development

Abstract: Little is known about the timing of the maternal-to-zygotic transition during seed development in flowering plants. Because plant embryos can develop from somatic cells or microspores, maternal contributions are not considered to be crucial in early embryogensis. Early-acting embryo-lethal mutants in Arabidopsis, including emb30/gnom which affects the first zygotic division, have fuelled the perception that both maternal and paternal genomes are active immediately after fertilization. Here we show that none of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
221
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(232 citation statements)
references
References 25 publications
9
221
1
1
Order By: Relevance
“…Further, the mosaic of epigenetic information carried by the male and female gametic genomes is likely to be complex and comprise not only imprinting marks, but systems of dosage compensation, and marking patterns that differentiate male from female chromosomes that enable a measured activation of the paternal genome post-fertilization (Vielle-Calzada et al 2000;Scholten et al 2002;Mosher et al 2009). An understanding of the epigenetic regulation of endosperm development, and indeed the validity of the kinship theory, must thus await unequivocal data on the overall maternal, paternal and bi-allelic input into early seed development and its consequences in terms of the expression of genes that directly results in the complex phenotypes involved, The kinship theory holds that the evolutionary interests of the male genome will be for the formation of a larger and very fit endosperm, and for the female genome a successful endosperm-but of fitness equivalent to its immediate sibs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the mosaic of epigenetic information carried by the male and female gametic genomes is likely to be complex and comprise not only imprinting marks, but systems of dosage compensation, and marking patterns that differentiate male from female chromosomes that enable a measured activation of the paternal genome post-fertilization (Vielle-Calzada et al 2000;Scholten et al 2002;Mosher et al 2009). An understanding of the epigenetic regulation of endosperm development, and indeed the validity of the kinship theory, must thus await unequivocal data on the overall maternal, paternal and bi-allelic input into early seed development and its consequences in terms of the expression of genes that directly results in the complex phenotypes involved, The kinship theory holds that the evolutionary interests of the male genome will be for the formation of a larger and very fit endosperm, and for the female genome a successful endosperm-but of fitness equivalent to its immediate sibs.…”
Section: Discussionmentioning
confidence: 99%
“…Expression analyses from Arabidopsis and maize (Zea mays) have shown that transcripts detected during early seed development, up to 3 d after pollination (DAP), are predominantly maternal (Vielle-Calzada et al, 2000;Grimanelli et al, 2005). This has been observed in both the embryo and the endosperm and raised the suggestion that early seed development might depend strongly on maternal transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the embryo phenotype, siliques from grp23 heterozygous plants were dissected with hypodermic needles and cleared in Herr's solution containing lactic acid:chloral hydrate:phenol:clove oil:xylene (2:2:2:2:1, w/w) (Herr, 1971;Vielle-Calzada et al, 2000). Embryo and endosperm development was studied microscopically with a Zeiss Axioskop II microscope equipped with differential interference contrast optics.…”
Section: Phenotypic Analysismentioning
confidence: 99%